Inheritance of Striga resistance in cowpea genotype B301 - Singh, B.; Emechebe, A. (Wiley, 1990)
The parasitic weed, Striga gesnerioides (Willd.) Vatke, is a major constraint in cowpea [Vigna unguiculata (L.) Walp.] production semi-arid regions of sub-Sahara Africa. Several sources of resistance have been identified. Of these, B301 has shown complete resistance to Striga across several countries. This study was undertaken to elucidate the genetics of Striga resistance in this line so that it can be effectively used in breeding programs. It was crossed to a susceptible cultivar, IT84S-2246-4. Parental, F1, F2, and backcross seeds were screened for Striga infection using pot-culture technique. Roots of each plant were washed free of soil and examined for Striga attachment. All 52 plants of B301 were completely free from Striga, whereas all 50 plants of IT84S-2246-4 were infected. All the 13 F1 plants and 47 backcross F1 plants involving B301 were also completely free. The backcross Ft plants involving IT84S-2246-4 segregated into .15 resistant: 14 susceptible ratio, whereas the F: plants segregated into 142 resistant and 47 susceptible, giving a close fit to 1:1 and 3:1 ratios, respectively. These data indicate a monogenic dominant inheritance for resistance to Striga in cowpea for which the gene symbol Rsg (resistance to S. gesnerioides) is assigned.